Preliminary insights on the metabolomics of Trichinella zimbabwensis infection in Sprague Dawley rats using GCxGC-TOF-MS (untargeted approach) - Ndlovu, I. S.; Silas, Ekuyikeno; Tshilwane, S. I.; Chaisi, M.; Vosloo, A.; Mukaratirwa, S. (Frontiers in Molecular Biosciences, 2023)
Trichinella infections have been documented globally and have been detected in wild and/or domestic animals except Antarctica. There is paucity of information in the metabolic responses of hosts during Trichinella infections and biomarkers for infection that can be used in the diagnosis of the disease. The current study aimed to apply a non-targeted metabolomic approach to identify Trichinella zimbabwensis biomarkers including metabolic response from sera of infected Sprague-Dawley rats. Fifty-four male Sprague-Dawley rats were randomly assigned into T. zimbabwensis infected group (n = 36) and the non-infected control (n = 18). Results from the study showed that the metabolic signature of T. zimbabwensis infection consists of enriched methyl histidine metabolism, disturbance of the liver urea cycle, impeded TCA cycle, and upregulation of gluconeogenesis metabolism. The observed disturbance in the metabolic pathways was attributed to the effects caused by the parasite during its migration to the muscles resulting in downregulation of amino acids intermediates in the Trichinella-infected animals, and therefore affecting energy production and degradation of biomolecules. It was concluded that T. zimbabwensis infection caused an upregulation of amino acids; pipecolic acid, histidine, and urea, and upregulation of glucose and meso-Erythritol. Moreover, T. zimbabwensis infection caused upregulation of the fatty acids, retinoic acid, and acetic acid. These findings highlight the potential of metabolomics as a novel approach for fundamental investigations of host-pathogen interactions as well as for disease progression and prognosis.